Hate and Identity - A social philosophical attempt to understand extremism - Gule, Lars (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2019)
In the analyses of extremism, the focus has mostly been on ideology and sociological – or so-called vulnerability – factors. While these factors are important the relevance and weight of emotions in the extremisation processes have not received the attention, they deserve. This article is an attempted to filling this gap. The paper explores the importance of emotions, especially strong emotions like hate and ‘ressentiment’, in establishing and reproducing the extremist identity. Methodologically this contribution emphasises a hermeneutic approach and draws on the philosophy of emotions, especially the approach of Robert C. Solomon. Empirically the article draws upon established international research and the author’s research on Islamist extremism in Norway.